Similarities and Disparities of Ghosts in Eastern and Western Literature Based the Novels Liaozhai Zhiyi, Dracula, dan a Christamas Carol - Cendrawaty Tjong; Raina Ophelia Sunggiardi; Vania Vania (Bina Nusantara University, 2010)
Ghosts is one of life unexplained phenomena also interesting theme for entertainment and literature materials. Every nation have their own ghost literature that reflects the nation’s view on ghost itself. This article compares China’s Liaozhai Zhiyi, Western’s Dracula and A Christmas Carol as representations of both culture. The writer through desktop study method found that culture influenced and shaped ghost image in the mind of novel writer. This leads to different image of ghost in the two cultures. The results is: ghost in two cultures appear mostly in the night time, have different types and classifications, different physical images, different way of thinking and how to handle ghosts.